Integrasi Nilai Pancasila Dalam Kepemimpinan Kepala Sekolah di SMAN 2 Ponorogo - Pamungkas, Wahyu Aji; Sulton (Universitas Muhammadiyah Ponorogo, 2026)
This research aims to analyze the integration of Pancasila values in the leadership of the Principal at SMAN 2 Ponorogo. Amidst the challenges of moral degradation and national identity crisis, the role of the school principal as a moral institution is crucial in internalizing national ideology into school culture. This research uses a descriptive qualitative approach with data collection through in-depth interviews, participatory observation, and documentation studies. The research results show that the integration of Pancasila values is carried out through a leadership-by-example strategy which includes three main dimensions: (1) The Divinity Dimension through consistent religious habituation as an ethical foundation; (2) The Democracy Dimension through participatory deliberation and consensus management; and (3) The Social Justice Dimension through the